Carbohydrate ingestion and soccer skill performance during prolonged intermittent exercise - Ali, A.; Williams, C. (Journal of Sports Sciences, 2009)
The aim of this study was to investigate the effect of ingesting a carbohydrate-electrolyte solution, during the 90-min Loughborough Intermittent Shuttle Test, on soccer skill performance. Seventeen male soccer players ingested either a 6.4 % carbohydrate-electrolyte solution or placebo solution equivalent to 8 ml/kg body mass before exercise and 3 ml/kg body mass after every 15 min of exercise, in a double-blind randomized cross-over design, with the trials separated by 7 days. The evening before the main trial, the participants performed glycogen-reducing exercise on a cycle ergometer (80 min at 70% VO2max) and were then fed a low-carbohydrate meal. After a 12-h overnight fast, they performed The Loughborough Soccer Passing Test before and after every 15 min of exercise. Analysis of the combined skill test data showed a significant time effect (P = 0.001) with differences between 0-45 and 75-90 min (P < 0.05). There was a 3 % reduction in skill performance from before to after exercise in the carbohydrate-electrolyte trial, whereas in the placebo trial the decrease was 14% (P = 0.07). In conclusion, skill performance during the simulated soccer activity appeared to deteriorate in the last 15-30 min of exercise. However, providing 52 g/h carbohydrate during exercise showed a tendency to better maintain soccer skill performance than a taste-matched placebo.